Theory of obstetrics: An epidemiologic framework for justifying medically indicated early delivery - Joseph K S (BMC, 2007)
Abstract Background Modern obstetrics is faced with a serious paradox. Obstetric practice is becoming increasingly interventionist based on empirical evidence but without a theoretical basis for such intervention. Whereas obstetric models of perinatal death show that mortality declines exponentially with increasing gestational duration, temporal increases in medically indicated labour induction and cesarean delivery have resulted in rising rates of preterm birth and declining rates of postterm birth. Other problems include a disconnection between patterns of gestational age-specific growth restriction (constant across gestation) and gestational age-specific perinatal mortality (exponential decline with increasing duration) and the paradox of intersecting perinatal mortality curves (low birth weight infants of smokers have lower neonatal mortality rates than the low birth weight infants of non-smokers). Discussion The fetuses at risk approach is a causal model that brings coherence to the various perinatal phenomena. Under this formulation, pregnancy complications (such as preeclampsia), labour induction/cesarean delivery, birth, revealed small-for-gestational age and death show coherent patterns of incidence. The fetuses at risk formulation also provides a theoretical justification for medically indicated early delivery, the cornerstone of modern obstetrics. It permits a conceptualization of the number needed to treat (e.g., as low as 2 for emergency cesarean delivery in preventing perinatal death given placental abruption and fetal bradycardia) and a calculation of the marginal number needed to treat (i.e., the number of additional medically indicated labour inductions/cesarean deliveries required to prevent one perinatal death). Data from the United States showed that between 1995-96 and 1999-2000 rates of labour induction/cesarean delivery increased by 45.1 per 1,000 and perinatal mortality decreased by 0.31 per 1,000 total births among singleton pregnancies at > = 28 weeks of gestation. The marginal number needed to treat was 145 (45.1/0.31), showing that 145 excess labour inductions/cesarean deliveries in 1999-2000 (relative to 1995-96) were responsible for preventing 1 perinatal death among singleton pregnancies at > = 28 weeks gestation. Summary The fetuses at risk approach, with its focus on incidence measures, provides a coherent view of perinatal phenomena. It also provides a theoretical justification for medically indicated early delivery and reconciles the contemporary divide between obstetric theory and obstetric practice.